(untitled) (Research, Society and Development, 2024)
Objective: To share the experience of implementing the Reception team with Risk Classification in an Obstetric and Gynecological Urgency and Emergency Service of a University Hospital in the Southern Region of Brazil, highlighting the transformations in the work process after implementation, the interaction of the teams involved with the care process, its acceptance and improvements to the care flow. Method: This is an experience report, experienced by a classifying nurse who shared the process of implementing Reception with Risk Classification and the impacts inherent to implementing this implementation, in an Obstetric and Gynecological Urgency and Emergency Service of a Hospital University in the Southern Region of Brazil, which took place in 2020. Results and Discussion: the implementation process resulted in transformations in the work process inherent to the implementation of this implementation, which promoted agility in the care of women who sought care, culminating in the humanization and safety of care, making care more effective and resolving. Conclusion: The study contributes to highlighting the importance of implementing risk classification as a practice that improves the quality of care and safety of care. The importance of carrying out continuing education throughout the process was noted, as well as the relevance of promoting improvements in relation to dialogue between care teams.